Extranodal MALT Lymphoma of the Right Triceps Muscle following Influenza Vaccine Injection: A Rare Case with an Interesting Presentation. (9th June 2011) - Edwards-Bennett, S. M.; Straus, D.; Athanasian, E. A.; Yahalom, J.
Abstract : The study describes a case of a 67-year-old female who developed a Stage I E marginal zone lymphoma of the right triceps muscle 1 month after influenza vaccination at the same site. She was treated with single modality, involved field radiation therapy (IFRT) to 4000 cGy in 20 fractions with excellent response and no evidence of disease after one year followup.